(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
The genotoxicity of soil pollution by heavy metals in Yerevan city with the application of Trad-SH (stamen hairs) and Trad-MN (micronuclei in tetrads of microspores) tests of Tradescantia (clone 02) was investigated. Possible contri-bution of heavy metals contents in soil samples from different regions of the city was taken into account as well. The highest level of genotoxity was marked in the soil samples from Proshian, Leningradian and Azatamartiknery streets, and lowest – A. Manoogian and Tsarav Akhbyur streets. The results obtained were shown to correlate with heavy metals concentration in soil samples.